Spatiotemporal Dynamics of Marine Heatwaves and Ocean Acidification Affecting Coral Environments in the Philippines - Rose Angeli Tabanao Macagga; Po-Chun Hsu (Remote Sensing)
The coral reefs in the Philippines are facing an unprecedented crisis. This study, based on a comprehensive analysis of marine heatwaves (MHWs), degree heating weeks (DHWs), and ocean acidification (OA) indices derived from satellite observations and reanalysis data, reveals how thermal stress and OA have progressively eroded coral ecosystems from 1985 to 2022. This study analyzed 12 critical coral habitats adjacent to the Philippines. The monthly average sea surface temperature (SST) in the study area ranged from 26.6 °C to 29.3 °C. The coast of Lingayen Gulf was identified as the most vulnerable coral reef site in the Philippines, followed by Davao Oriental and Polillo Island. The coast of Lingayen Gulf recorded the highest total MHW days in 2022, amounting to 293 days. The coast of Lingayen Gulf also reached the highest DHW values in July and August 2022, with 8.94 °C weeks, while Davao Oriental experienced the most extended average duration of MHWs in 2020, lasting 90.5 days per event. Large-scale climate features such as the El Niño–Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) significantly influenced the study area’s SST anomalies and MHW events. High-risk coral bleaching periods, such as 1988–1989, 1998–1999, 2007–2008, and 2009–2010, were characterized by transitions from El Niño and positive PDO phases, to La Niña and negative PDO phases. However, since 2015, global warming has led to high cumulative heat stress without specific climate background patterns. We propose a Coral Marine Environmental Vulnerability Index (CoralVI) to integrate the spatiotemporal dynamics of warming and acidification and their impacts on coral habitats. The data show a rapid increase in the marine environmental vulnerability of coral habitats in the Philippines in recent years, extending to almost the entire coastline, posing significant threats to coral survival.